MACHINE LEARNING: AN OVERVIEW - Trisal, Adya; Mandloi, Dheeraj (International Journal of Research -GRANTHAALAYAH, 2021)
Given the tremendous availability of data and computer power, there is a resurgence of interest in using data driven machine learning methods to solve issues where traditional engineering solutions are hampered by modeling or algorithmic flaws. The purpose of this article is to provide a comprehensive review of machine learning, including its history, types, applications, limitations and future prospects. In addition to this, the article also discusses the main point of difference between the field of artificial intelligence and machine learning.